Perbedaan Kelembaban, Kepadatan Hunian, Ventilasi Rumah terhadap Kejadian Infeksi Saluran Pernafasan Akut pada Balita - Dina Arihta Tarigan; Eli Heryanti (Jurnal Health Sains, 2021)
The incidence of Acute Respiratory Infection (ARI) is one of the main causes of illness in children under five in developing countries. Likewise in the working area of the Klapanunggal Health Center. This condition can be seen from the first prevalence of ARI, which always increases and is the first of the top ten based on the annual report of the Puskesmas. This study aims to determine the relationship between the physical conditions of the home environment which includes occupancy density, humidity, house ventilation with the incidence of ARI. This research was conducted in August 2020 in Klapanunggal District. This type of research uses a cross sectional approach. The subjects studied were all houses in which there were toddlers aged zero to five years with a sample size of 97 respondents. Data collection through structured interviews, observation. Statistical test using kai quadaract test. The results of the study showed that there was a relationship between occupancy density (OR = 8.254, p = 0.001), home ventilation (OR = 2.625, p = 0.003), and humidity (OR = 3.010, p = 0.018) with the incidence of ARI. Based on this research, an effort to reduce the incidence of ARI in children under five is to provide counseling to the community to improve the quality of housing and disseminating information about poor indoor air quality that can cause confusion with ISPA.